2019
DOI: 10.1590/0103-8478cr20180306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nitrification process in a culture of pacific white shrimp, using artificial substrate and bacterial inoculum in a biofloc technology system (BFT)

Abstract: Litopenaeus vannamei is the most cultured marine shrimp in all types of systems including the Bioflocs Technology System (BFT). Bioflocs are formed by microorganisms, among these, autotrophic bacteria are responsible for the nitrification process. This study aimed to identify and promote the development of nitrifying bacteria by adding artificial substrates and biofloc inoculum in L. vannamei culture in a BFT system. The experiment consisted of four treatments with three replics (4x3) as follows: (1) Control: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…We observed that the nitrification process was efficient during the experimental period, with higher concentrations of NO − 3 -N compared with TAN and NO − 2 -N. This efficiency is related to the combination of fertilization using anaerobic and aerobic processes in rice bran by microorganisms (Romano et al, 2018). In addition, the use of artificial substrate and biological activator probably have accelerated the system's nitrification processes (Santos et al, 2019;Silva Neto et al, 2012). concentration range for systems that use low-salinity water (<0.81 mg TAN/L and <0.45 mg NO − 2 -N/L; Gross et al, 2004;Lin & Chen, 2001;Valencia-Castañeda et al, 2018).…”
Section: Water Qualitymentioning
confidence: 78%
See 1 more Smart Citation
“…We observed that the nitrification process was efficient during the experimental period, with higher concentrations of NO − 3 -N compared with TAN and NO − 2 -N. This efficiency is related to the combination of fertilization using anaerobic and aerobic processes in rice bran by microorganisms (Romano et al, 2018). In addition, the use of artificial substrate and biological activator probably have accelerated the system's nitrification processes (Santos et al, 2019;Silva Neto et al, 2012). concentration range for systems that use low-salinity water (<0.81 mg TAN/L and <0.45 mg NO − 2 -N/L; Gross et al, 2004;Lin & Chen, 2001;Valencia-Castañeda et al, 2018).…”
Section: Water Qualitymentioning
confidence: 78%
“…This efficiency is related to the combination of fertilization using anaerobic and aerobic processes in rice bran by microorganisms (Romano et al, 2018). In addition, the use of artificial substrate and biological activator probably have accelerated the system's nitrification processes (Santos et al, 2019; Silva Neto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results are an indicative of the presence of two main groups responsible for the nitrification process: autotrophic bacteria, known as AOB and NOB; and nitrifying heterotrophic bacteria. Santos et al (2019) found a greater number of nitrifying bacteria, compared with heterotrophic bacteria, in artificial substrates (bioballs) in the culture of pacific white shrimp (Litopenaeus vannamei Boone, 1931).…”
Section: Resultsmentioning
confidence: 99%
“…Each experimental unit had a heating system (Roxin HT1300, 100 W) for thermal control (27°C), and aeration was provided through a porous hose (15 cm, Aero-tube TM, Swan, Marion, OH) individually connected to a blower (CR8, 7.5 CV, Ibram). The tanks were filled with 80% (40 L) of chlorinated (20 mg•L -1 active chlorine) seawater (salinity 30.38 g•L -1 ) and dechlorinated with constant aeration, and subsequently with 20% (10 L) of previously matured biofloc inoculum, according to the method proposed by Santos et al (2019), in order to ensure the following initial conditions: 0.07 ± 0.04 mg•L -1 TAN, 0.05 ± 0.01 mg•L -1 NO 2 --N, 15.27 ± 2.77 mg•L -1 NO 3 --N, 164.1 ± 12.6 mg•L -1 CaCO 3 , and 137.10 ± 28.70 mg•L -1 SST. In addition, the photoperiod was controlled and maintained at 12:12 light:dark.…”
Section: Origin Of Animal and Facilitiesmentioning
confidence: 99%